ANALYSIS OF FACTORS CONTRIBUTING TO PULMONARY TUBERCULOSIS INCIDENCE AT UPTD HEALTH CENTER SIDORAHAYU, PLAKAT TINGGI DISTRICT, MUSI BANYUASIN REGENCY - Ida Royani; Akhmad Dwi Priyatno; Gema Asiani; Syahrizal; Hermanto (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
Mycobacterium tuberculosis, better known as tuberculosis (TB), is an infectious disease that attacks the body system through the lungs. Based on data from the Care Detection Rate (CDR) of Tuberculosis Cases at the UPTD Puskesmas Sidorahayu, the number of positive Tuberculosis cases from 2023 to 2025 has increased. Where in 2023 the number of Tuberculosis cases was 15 cases and in 2024 the number of Tuberculosis cases was 19 cases and in 2025 there were 20 cases. The achievement of the discovery of suspected tuberculosis in 2023 amounted to 147 cases and in 2024 amounted to 178 cases, while in 2025 the number of suspected tuberculosis cases amounted to 46 cases. The purpose of this study was to analyze the picture of the incidence of pulmonary tuberculosis (TB) at the UPTD Puskesmas Sidorahayu in 2025. Research methodology with a Quantitative approach with a cross-sectional study, the research was conducted in May 2025 at UPTD Puskesmas Sidorahayu. The population in this study amounted to 263 which was obtained from positive patients and suspected Tuberculosis patients who received treatment at the Sidorahayu UPTD Puskesmas from 2024-2025, sampling techniques with Purposive sampling using the slovin formula obtained 72 samples, with Univariate, Bivariate, Multivariate data analysis with Chi-Square Test. The results obtained pvalue variable age 0.515, gender 0.206, education 0.328, income 0.792, ventilation 0.025 occupancy density 0.006, humidity 0.004, temperature 0.004, lighting 0.025. In conclusion, there is a significant relationship between ventilation, occupancy density, humidity, temperature, and lighting with the incidence of TB while the variables of age, gender, education, income have no significant relationship with the incidence of TB. The most dominant variable is lighting.UPTD Puskesmas Sidorahayu needs to provide clear and easy-to-understand information to the community about environmental risk factors that can trigger Tuberculosis, such as occupancy density, poor ventilation, poor lighting, and high humidity.